1987
DOI: 10.7326/0003-4819-106-3-386
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Prognosis of Brain Metastases in Small Cell Lung Cancer

Abstract: Brain metastases are found at diagnosis in 10% of patients with small cell lung cancer. To clarify the effect of central nervous system metastases on prognosis, the records of 429 patients with small cell lung cancer were reviewed. Forty-three patients (10%) presented with brain metastases. In 18 patients the brain was the only site of metastatic disease, whereas the remaining 25 patients had at least one additional metastatic site. Forty-one of forty-three patients were treated with combination chemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…We cannot comment directly on response duration because the study design included the option of cranial irradiation for patients who had responded to chemotherapy. The policy of chemotherapy as initial treatment for brain metastases has not been compared with initial radiotherapy in a randomised trial, but we have not found evidence of a detriment in survival (Cox et al, 1980;Giannone et al, 1987).…”
Section: Response To Chemotherapymentioning
confidence: 76%
“…We cannot comment directly on response duration because the study design included the option of cranial irradiation for patients who had responded to chemotherapy. The policy of chemotherapy as initial treatment for brain metastases has not been compared with initial radiotherapy in a randomised trial, but we have not found evidence of a detriment in survival (Cox et al, 1980;Giannone et al, 1987).…”
Section: Response To Chemotherapymentioning
confidence: 76%
“…Promptly she developed 2 brain metastases 8 months after diagnosis and had to undergo therapeutic irradiation. In several studies there was no significant influence of central nervous system metastases on survival, because the patient died earlier from extracerebral disease [2,10,11]. However, patients presenting with brain metastases showed much better survival times than those with delayed development of brain metastases, median survival times of 7 and 3 months, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…Only 20% achieve a complete neurological recovery [13]. 65% of the patients who benefit from the irradiation endure a cerebral relapse before their death [11]. Nevertheless, long-term survivors with brain metastases are described in different studies: In the overview by Lassen et al [2], 107 patients showed brain metastases at the time of diagnosis, 3 of them survived more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The standard therapeutic approach for limited disease is chemotherapy using cisplatinum and etoposide (EP) with concurrent thoracic irradiation. Because EP is relatively well tolerated in combination with radiation, it is preferred over CAV in this setting [45]. Chemotherapy alone does not offer good local control, with local failure rates of 75-90% despite good initial response rates of 80-90%.…”
Section: First-line Therapy In Stage I-iiib (Ld)mentioning
confidence: 99%
“…The alkaloid topotecan is a topoisomerase inhibitor approved by the US Food and Drug Administration for the second-line therapy of SCLC [45,61]. It has also been investigated for use as a first-line agent.…”
Section: Newer Chemotherapeutic Agentsmentioning
confidence: 99%